Biological Effects of Culture Substrates on Human Pluripotent Stem Cells - Yohei Hayashi; Miho Kusuda Furue (Stem Cells International)
In recent years, as human pluripotent stem cells (hPSCs) have been commonly cultured in feeder-free conditions, a number of cell culture substrates have been applied or developed. However, the functional roles of these substrates in maintaining hPSC self-renewal remain unclear. Here in this review, we summarize the types of these substrates and their effect on maintaining hPSC self-renewal. Endogenous extracellular matrix (ECM) protein expression has been shown to be crucial in maintaining hPSC self-renewal. These ECM molecules interact with integrin cell-surface receptors and transmit their cellular signaling. We discuss the possible effect of integrin-mediated signaling pathways on maintaining hPSC self-renewal. Activation of integrin-linked kinase (ILK), which transmits ECM-integrin signaling to AKT (also known as protein kinase B), has been shown to be critical in maintaining hPSC self-renewal. Also, since naïve pluripotency has been widely recognized as an alternative pluripotent state of hPSCs, we discuss the possible effects of culture substrates and integrin signaling on naïve hPSCs based on the studies of mouse embryonic stem cells. Understanding the role of culture substrates in hPSC self-renewal and differentiation enables us to control hPSC behavior precisely and to establish scalable or microfabricated culture technologies for regenerative medicine and drug development.